Origin, Evolution and Current State Russian-Chinese Foreign Trade Relations - L. V. Dobrovolsky; A. S. Nogmova (Проблемы постсоветского пространства, 2023)
The article examines Russian-Chinese foreign trade relations, their origin, development and current state. The official approaches of the states to the organization, subsequent development and strengthening of foreign trade relations, established by Nerchinsky (1689), Kyakhtinsky (1727), Tianjin (1858), Beijing (1860), Moscow (1896) are given contracts and other documents. The current state, indicators of the Russian-Chinese foreign trade turnover in 2020–2022 are disclosed. and priority areas of mutual foreign economic cooperation between states. The main projects of investment cooperation are given. The conclusions summarize the impact of Russian-Chinese foreign trade cooperation on improving the efficiency of the implementation of programs for their socio-economic development.